Synthesis, characterization and electrical and CO2 sensing properties of triazine containing three dendritic phthalocyanine - (:unkn) unknown (ELSEVIER SCIENCE SA, 2005)
The metal-free phthalocyanine la was synthesised by statistically mixed condensation of 4-nitrophthalonitrile and 4-(2-dimethylan- noethylsulfanyl)phthalonitrile in dry 2-(dimethylamino)ethanol. The same route were applied to prepare metal -containing phthalocyanines using metal salts Zn(OAC)(3)center dot 2H(2)O and CoCl2, respectively, in dry DMF. The nitro compounds were reduced to amine with sodium sulfide and quarternized by reaction of MeI. These compounds were then reacted with cyanuric chloride in the presence of potassium carbonate as a base in mixture of THF and DMF gave s-triazine containing three amino phthalocyanines 4a-c. The reaction of three phthalocyanines with sodium salt of triethylmethanetricarboxylate in absolute ethanol were synthesised first generation of dendrimer 5a-c. The second generation of dendritic phthalocyanines 6a-c were prepared by the reaction of dentritic phthalocyanines with tris (H2NC(CH2OH)(3)) using K2CO3 as a base in DMSO. The dendritic phthalocyanines containing tris are slightly soluble in water. The new compounds were characterized by elemental analysis and UV-vis, IR, NMR spectra. The temperature dependence of the dc and ac conductivity of these compounds and the adsorption Of CO2 gas on thin film of the compounds were investigated by dc conductivity and impedance spectroscopy technique using an interdigital transducer structure on glass substrate. While exposure to CO2 have no influence on the electrical conductivity (ac and dc) of compound 6a and 6c, the conductivity of the film of 6b strongly depend on the presence of the CO2 gas. Completely reversible sensor signals were obtained for compound 6b. The impedance spectra were obtained at frequencies between 40 and 10(5) Hz, and in a wide range Of CO2 concentrations (from 500 to 8000 ppm) at room temperature. The temperature dependence of dc conductivity show typical Arrehenius behaviour for all compounds. The ac conductivity of the films is represented by the form omega(s). The dependency of frequency exponent s on temperature suggests a correlated barrier hopping (CBH). (C) 2005 Elsevier B.V. All rights reserved.
Keywords: dendritic phthalocyanine; s-triazine; CO2 sensing; CBH; ARYL ETHER DENDRIMERS; COPPER PHTHALOCYANINE; THIN-FILMS; MU-M; SENSOR; GAS